2022
DOI: 10.24931/2413-9432-2021-9-4-4-22
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implementation and scientific development of photodynamic therapy in Russia in 2010-2020

Abstract: In recent years, the development of methods of photodynamic therapy (PDT) and photodynamic photodiagnostics (PD) in Russia is characterized by an intensive rise, steadily growing interest of specialists from various medical specialties in the method of specialists from various medical specialties, an increase in the level of equipment number of hospitals with the necessary equipment for performing PD and PDT, the and the emergence of new photosensitizers on the pharmaceutical market, and an increasing increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Photodynamic therapy (PDT) is a relatively new and promising method for the treatment of malignant tumors. Despite the achievements in cancer treatment by standard methods (surgery, radiation therapy, chemotherapy), certain problems, such as resistance of tumor cells, metastasis, and, as a consequence, recurrence of the disease, have not been solved yet [ 1 , 2 , 3 , 4 ]. PDT is advantageous over traditional treatment methods because it is localized (the cytotoxic effect develops in the irradiated area only), making it possible to overcome multiple drug resistance (MDR) of tumor cells, activate the body’s immune response, and prevent surgical risks and severe systemic complications, and the cost of treatment is low [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Photodynamic therapy (PDT) is a relatively new and promising method for the treatment of malignant tumors. Despite the achievements in cancer treatment by standard methods (surgery, radiation therapy, chemotherapy), certain problems, such as resistance of tumor cells, metastasis, and, as a consequence, recurrence of the disease, have not been solved yet [ 1 , 2 , 3 , 4 ]. PDT is advantageous over traditional treatment methods because it is localized (the cytotoxic effect develops in the irradiated area only), making it possible to overcome multiple drug resistance (MDR) of tumor cells, activate the body’s immune response, and prevent surgical risks and severe systemic complications, and the cost of treatment is low [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Light absorption of biological tissues in this window is minimal, thus allowing deeper light penetration through the tissue, and, as a result, higher therapeutic effectiveness. There is an increasing interest in bacteriochlorin-based photosensitizers as fluorescent probes and medicines for diagnostics and treatment, because their NIR fluorescence and efficient singlet oxygen generation properties are advantageous both for imaging and photodynamic therapy [4][5][6][7][8][9][10]. The most important characteristics of these PSs are their rapid clearance from circulation and their minimum skin-phototoxicity induced by visible light.…”
Section: Introductionmentioning
confidence: 99%
“…By the end of the study, complete regression was observed in 88.9% of rats, and inhibition of tumor growth was found in 99.9% of the animals. Based on the results of that study, the authors concluded that the combination of photodynamic therapy with cisplatin chemotherapy was a more efficient treatment method compared with each therapy alone [ 2 ].…”
Section: Introductionmentioning
confidence: 99%